The role of glucose disposal efficiency in predicting stroke among older adults: a cohort study - Zhao, Zongren; Liu, Yu; Zheng, Jinyu; Li, Jing (Frontiers in Neurology, 2025)
BackgroundGlucose disposal rate (eGDR) has recently been validated as a surrogate marker of insulin resistance, providing a novel approach to assess metabolic health. However, the relationship between changes in eGDR levels and stroke incidence remains underexplored. The current study aims to investigate the impact of eGDR control on stroke incidence and related events.MethodsData were obtained from the China Longitudinal Study on Health and Retirement (CHARLS). The analysis included 6,375 participants aged 45 and above with complete stroke and eGDR data from the CHARLS for 2011, 2013, and 2015. Logistic multivariable regression examined the relationship between eGDR and stroke, using threshold analysis to identify inflection points. we categorized participants into distinct subgroups based on sociodemographic variables to see the relationship between stroke and other variables.ResultsOut of the 8,060 individuals analyzed in the cohort, 821 were diagnosed with new-onset stroke. There was a notable negative correlation found between new-onset risk of stroke and eGDR, with each Interquartile Range (IQR) increment in eGDR leading to a 38% risk reduction [OR: 0.62; 95% CI: (0.45,0.84)]. Stratified analyses revealed age as a potential modifier in the age-stroke relationship (P for interaction = 0.01).ConclusionPoorly controlled eGDR level is associated with an increased risk of stroke in middle-aged and elderly people. Monitoring changes in eGDR may help identify individuals at high risk of stroke early.